Plakat "Nase voll von dieser Stadt? Wir haben noch 30 andere."
soziale Fragen;Bevölkerung;Bevölkerungsaufbau;Altersgliederung;junger Mensch soziale Fragen;Leben in der Gesellschaft (allgemein);Freizeit;Tourismus;Reiseagentur soziale Fragen;Raumplanung und Wohnungswesen;Ortschaft;Agglomeration;Stadt soziale Fragen;Bevölkerung